The EU digital strategy between sovereignty and green transformation: Political milestones, policy fields and strategic narratives - Wulf Reiners; Matthias Kachelmann (German Institute of Development and Sustainability (IDOS), 2025)
Accelerated by the COVID-19 pandemic and technological developments such as artificial intelligence, digital transformations affect almost all areas of social, economic, and environmental life. Emerging as a tool for addressing challenges - but also as a source of new problems or as an amplifier of existing challenges - digital transformation has increasingly become the focus of initiatives at the European Union (EU) level. Since 2015, the EU has developed a comprehensive digital agenda spanning various policy domains, ranging from bolstering the single market to addressing foreign and security policy concerns. This paper examines the evolving landscape of digitalisation-related EU policies through the lens of strategy documents and policy guidelines, with particular emphasis on developments between 2020 and 2025. It explores the EU's overarching approach towards digitalisation - its conceptualisation, objectives, and self-defined role in shaping the digital revolution. The analysis reveals that the EU addresses digitalisation through a multitude of policy-specific strategies and guidelines, characterised by four predominant strategic narratives: A geopolitical ("digital sovereignty"), an environmental ("twin transitions"), a socio-political ("fundamental rights"), and an economic ("growth and competitiveness") narrative.
Keywords: 320; Digitalisation; digital strategy; digital transformation; EU; EuropeanUnion; narrative; strategy; sovereignty; GreenDeal; AI